THE INFLUENCE OF GOOD GOVERNANCE, ORGANIZATIONAL CULTURE AND INTERNAL CONTROL SYSTEMS ON ORGANIZATIONAL PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING - Amna Farida; Nur Faliza; Yanita; Faisal Matriadi; Aiyub; Mariyudi (CV. Radja Publika, 2024)
This research aims to examine the influence of Good Governance variables, Organizational Culture and Internal Control Systems on Organizational Performance with Organizational Commitment as a Mediating Variable in Bener Meriah Regency Regional Work Units. And the data was analyzed using a path analysis tool with the SEM Amos Version 25 program. The research results showed that the variables good governance, organizational culture, internal control system had a significant effect on organizational commitment and SKPD performance in Bener Meriah Regency. Then organizational commitment was also found to influence SKPD performance. Furthermore, in the analysis of indirect effects through mediation effect testing, it was found that organizational commitment mediates the relationship between good governance, organizational culture and internal control systems on SKPD performance, both fully (full mediation) and partially (partial mediation). It is hoped that the results of this research will provide a real contribution to organizational leaders in efforts to improve organizational performance in the future.written in a single paragraph is, no more than 200 words. (Times New Roman 11, single space, and italics).